Spatial Reasoning Based on 3D-ICSRM Model. (18th July 2019) - Liu, Yongshan; Gong, Xiang; Kong, Dehan
Abstract : The existing spatial relationship composite models have defects in both cognitive habits and differentiation degree when describing the spatial relationship between the three dimensional objects. These defects can cause inaccuracy in the process of spatial reasoning. In order to solve this problem, this paper proposes a Three-Dimensional Improved Composite Spatial Relationship Model (3D-ICSRM). Then a high-precision spatial relationship reasoning algorithm is presented based on this model, which combines qualitative and quantitative analyses. Finally, both the correctness and performance advantages of spatial reasoning algorithm are verified by experiments based on this proposed model.